2015
DOI: 10.3329/cardio.v7i2.22259
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Cardiac Disease at Coronary Care Unit of Dhaka Medical College Hospital

Abstract: Background: Epidemiological transition which is taking place in every part of the world, among all races, ethnic groups and cultures has resulted in the global rise in cardiovascular disease (CVD). Cardiovascular disease is the leading cause of morbidity and mortality throughout the world. We tried to assess the pattern of cardiac disease at coronary care unit (CCU) of tertiary care hospital. Methods: A cross sectional study conducted among the patients admitted at CCU of Dhaka Medical College Hospital (DMCH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…This finding was not in agreement with studies conducted in northern Malawi, Addis Ababa, Jimma, and the same institution two decades ago, which concluded that rheumatic heart disease was the leading cause of heart disease followed by hypertensive heart disease 3,11,13,19,20. The leading cardiac disease etiologies identified by the study performed in Bangladesh were IHD, HF, and chronic RVHD 21. In this study, hypertensive heart disease had surpassed rheumatic heart disease as the leading heart disease.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This finding was not in agreement with studies conducted in northern Malawi, Addis Ababa, Jimma, and the same institution two decades ago, which concluded that rheumatic heart disease was the leading cause of heart disease followed by hypertensive heart disease 3,11,13,19,20. The leading cardiac disease etiologies identified by the study performed in Bangladesh were IHD, HF, and chronic RVHD 21. In this study, hypertensive heart disease had surpassed rheumatic heart disease as the leading heart disease.…”
Section: Discussioncontrasting
confidence: 80%
“… 3 , 11 , 13 , 19 , 20 The leading cardiac disease etiologies identified by the study performed in Bangladesh were IHD, HF, and chronic RVHD. 21 In this study, hypertensive heart disease had surpassed rheumatic heart disease as the leading heart disease. This might be due to the increasing prevalence of hypertension, as supported by the high proportion of hypertension of approximately two thirds (62.3%) of CVDs found in this study.…”
Section: Discussionmentioning
confidence: 77%
“…5 Troponin (T or I), the biomarker of choice to diagnose myocardial necrosis, is often normal during the first few hours of STEMI, thus emergent percutaneous coronary intervention (PCI) can be helpful. 6 Whereas, unstable angina (UA) and non ST-elevation (NSTEMI) are caused by incomplete occlusion of the culprit artery in 60-90% of cases. 7 According to the World Health Organization, cardiovascular diseases are the leading causes of morbidity and mortality in 2020 worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…More recent data indicates CAD prevalence to be 3.4% in rural and 19.6% in an urban sample of working professionals 13,14 . In Bangladesh, ACS is the major presenting form of CAD and accounts for 45% of all cause cardiac hospitalization 15 .…”
Section: Introductionmentioning
confidence: 99%